Rosanilins: indicator dyes for chloramphenicol-resistant enterobacteria containing chloramphenicol acetyltransferase. - Proctor, G N (1982)
Rosanilin dyes such as crystal violet and basic fuchsin have been used as indicator dyes in solid growth medium for chloramphenicol-resistant enterobacterial colonies containing the enterobacterial resistance enzyme chloramphenicol acetyltransferase (CAT). On certain media containing rosanilins, cells containing CAT formed darker colonies than cells not containing CAT. Contrast was affected by the types and concentrations of complex nutrients, sugars salts, and rosanilin dyes present. When crystal violet was used as the indicator dye, contrast could not be obtained for strains whose growth was partially inhibited by crystal violet. Contrast could not be obtained between yeast colonies with and without the enterobacterial resistance enzyme, between Bacillus subtilis colonies with and without the staphylococcal resistance enzyme, or between enterobacterial colonies with and without the staphylococcal resistance enzyme. The darker coloration of enterobacterial colonies with the enterobacterial enzyme was due to the binding of dye to enzyme. Rosanilin dues have been used to score resistance phenotypes by colony color, to detect chloramphenicol-sensitive sectors in chloramphenicol-resistant colonies, and to screen for occasional chloramphenicol-sensitive cells in a resistant population during cloning by insertional inactivation of the chloramphenicol resistance gene.